Implementation of Microteaching Based on Self-Directed Learning - Fitri, Rika; Asril, Zainal; Sabri, Ahmad; Remiswal, Remiswal; Firdaus, Firdaus; Zalnur, Muhammad (International Journal of Islamic Studies Higher Education, 2025)
The development of a microteaching learning strategy based on self-directed learning in private Islamic religious universities is motivated by the fact that lecturers teaching microteaching courses still use monotonous and uninnovative teaching methods, and facilities and infrastructure are still limited, which has an impact on the quality of students' understanding of microteaching, resulting in students being less capable of teaching when they enter the field for practical training. This study aims to describe the application of microteaching based on Self-Directed Learning in supporting students' learning independence and enhancing their teaching competencies as prospective teachers. The study employs a qualitative method with a case study approach. Data sources were obtained through in-depth interviews with twelve informants. All data were analyzed thematically using the Miles & Huberman Interactive Analysis Model technique. The results of the study indicate that the implementation of microteaching based on Self-Directed Learning is able to encourage students to learn independently, develop reflective skills, and improve teaching abilities and critical thinking. Students demonstrated active engagement in planning, conducting teaching practices, and self-evaluation through feedback from peers and instructors. The learning modules used were deemed practical, systematic, and capable of facilitating a self-directed and focused learning process.